Influencia de la práctica de ordeño sobre el recuento de células somáticas (RCS) y unidades formadoras de colonias (UFC) en leche bufalina (2014)
The aim of an appropriate milking procedure is to reduce the risk of milk contamination. This work studied the risk factors in milking practices that affect the hygienic (CFU) and sanitary quality (SCC) of milk tanks from the “Mid Magdalena” and ”Atlantic Coast” regions of Colombia. A checklist that explored pre-milking, milking and post-milking activities as possible factors influencing CFU and SCC in 23 buffalo farms was applied. On the day of the checklist survey, samples of cold milk in tank to test for bacteria counts were taken, finding an average of 182.6 ± 295.4 x 103 CFU/mL; also tested for SCC was tested and an average of 137.1 ± 158.9 x 103 sc/mL was found. As hygienic quality protective factors generating a low CFU count in bulk tank floor tidiness, udder and teat washing, hand washing frequency, duration of teat sealing, wiping of sealing dip, presence of filter in the milk container, the use of disposable filters, milking the buffalo cows positive for mastitis towards the end of the milking process and cooling the milk at 4°C in less than 2 hours after milking was identified. The risk factors associated with high CFU counts are the absence of hands washing with OR (Odds Ratio) 1.7 (p= 0,003), teat sealing with OR 1.07 (p= 0,003), use of disposable filter in milk container, and the period of time between milking and tank storage with OR 1.83 (p= 0.4). The risk associated with high SCC ́s is material for hand drying with OR 1.04 (p= 0.002).